Wealth‐Based Water Rates—Really?. Issue 3 (1st March 2015) - Lafrance, David; Curtis, Tom
Abstract : Last month in this column the authors discussed the challenges of ensuring the affordability of water service and the USEPA's new framework for addressing this challenge. As promised, this month's column would discuss a concept that some are vetting: the water industry might solve its affordability concern by overhauling its existing rate architecture and replacing it with one in which the relatively affluent pay more for water and wastewater services, and those less financially fortunate pay less.